Assessing health risk reduction from road traffic noise: The impact of vehicle composition and traffic speed in the transition to electric vehicles – A prediction in Sapporo City, Japan - Farah Elida Selamat; Junta Tagusari (Hygiene and Environmental Health Advances)
Environmental noise poses a risk to public health. Recent societal shifts aimed at creating a low-carbon society are expected to change the acoustic landscape, such as the transition from internal combustion engine vehicles (ICEVs) to electric vehicles (EVs). However, the impact of transitioning to EVs on traffic conditions and health risk reduction remains uncertain. This study aims to evaluate traffic efficiency and clarify how shifting from ICEVs to EVs influences health risks associated with road traffic noise. We analysed the relationship between health risk reduction, vehicle composition (i.e., proportion/percentage of heavy vehicles), and traffic speed according to the CNOSSOS-EU noise emission model and the exposure-response functions provided in the Environmental Noise Guidelines by the World Health Organization Regional Office for Europe (WHO-EU). The results were validated by estimating the reduction of health risks in small and large urban areas using actual traffic conditions. The results of the calculations indicate that a greater percentage of heavy EVs and lower traffic speeds lead to a more significant reduction in health risks. In the two selected areas, the region with a higher proportion of heavy EVs achieved a risk reduction of 30–40 %, whereas the area with a lower percentage of heavy EVs experienced approximately a 20 % reduction. The reduction of each health risk in both areas was consistent with the calculation results. In Sapporo City, the health risk reduction was estimated to be 15—20 %. This study demonstrated that transitioning to EVs effectively reduces health risks associated with road traffic noise and identifies the optimal traffic conditions for minimizing these risks. Increasing the adoption of EVs could serve as a significant strategy for alleviating the health impacts of road traffic noise.